Potencial de mineralização de carbono e nitrogênio em solos do Semiárido Paraibano. - Barbosa, Maria Aparecida da Silva (2016)
The potential for mineralization of organic matter is an essential parameter for understanding the dynamics of C and N in the soil, especially when it emphasizes the semi-arid soils where there’s lacks of information about this phenomenon. This study aimed to evaluate the potential mineralization of C and N in 26 Paraíba semiarid soils. In incubation columns, respective samples to 26 Paraíba semiarid soils were incubated, and weekly until the period of 121 days were collected leachate material for the determination of C, N nitric and ammoniac. With bases in accumulated values in the time series, it was determined the parameters of the kinetic model, estimating the C emission, and N mineralization rate. It was concluded that: under favorable conditions, the emission of C-CO2 to atmosphere is increased until the 91 th day where the emission rate is greater than 99.1%, regardless of soil type; the potential emission of C-CO2 in the Paraiba semi-arid follows the order: Ferralsol > Vertisol > Regosol > Luvisol> Solonetz > Cambisol > Fluvisol> Litosol (FAO/WRB), with mean values of 954.65, 753.46, 590.27, 546.99, 427.97, 408.36, 388.19 and 340.95 mg g-1 soil, respectively; In mineralization of NO3-, all soils tended to stabilize at 56 (days) incubation with upper cumulative rate 96.1%, while the NH4+ ranged from soil, with values between 59.4 and 86.1% in the same period; C emission rate had great influence of soil chemical properties, especially effective CEC, the potential CEC, the sum of bases, and organic matter content; N mineralization rate had no significant difference between soils.